(untitled) (Jagannath University Journal of Life and Earth Sciences, 2025)
This study aims to explore the awareness, attitudes, and trust of residents living near the Rooppur Nuclear Power Plant regarding nuclear energy. The research specifically targets the community of BBC Bazar, a locality positioned near the boundary of this significant nuclear initiative and situated within the government-designated 3 km precautionary zone. For this analysis, eighty-three permanent residents—who are not involved with the nuclear power plant project and are aged 18 or older—were chosen as participants for data collection through structured questionnaires. Employing quantitative research methods, the study utilized statistical tools, including the chi-square test, Friedman’s test, and descriptive statistics, to analyze the gathered data. The findings reveal a predominant concern among residents for a reliable, cost-effective power supply, while their attitudes towards nuclear energy are markedly mixed. Notably, individuals with higher levels of education and income demonstrate a greater awareness of, and caution regarding, the potential risks associated with nuclear power. A significant number of participants reported a lack of familiarity with the emergency response plans in place and expressed a strong preference for evacuating the area in the event of a nuclear accident, highlighting underlying anxieties related to safety concerns. Interestingly, despite many respondents expressing general support for nuclear energy generation as a concept, there is a prevalent reluctance to host such projects in their immediate surroundings—a clear reflection of the NIMBY (Not in My Back Yard) sentiment. The study emphasizes the critical need for enhanced public engagement, transparent communication, and increased awareness programs to foster greater acceptance and ensure the safety of nuclear power plant projects throughout Bangladesh. By addressing these factors, the research aims to bridge the gap between community concerns and the advancement of nuclear energy initiatives. Jagannath University Journal of Life and Earth Sciences, 10(1) 59-75